2009
DOI: 10.1680/ensu.2009.162.2.67
|View full text |Cite
|
Sign up to set email alerts
|

Full-scale testing to assess climate effects on embankments

Abstract: A unique facility for engineering and biological research has been established with the aim of improving fundamental understanding of the effects of climate change on slopes. This paper describes the building and monitoring of a full-scale embankment representative of UK infrastructure, the planting and monitoring of representative vegetation, and the construction of a system of sprinklers and covers to control climate. A summary of the results of the first experiments simulating predicted future UK climate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 7 publications
(6 reference statements)
0
37
0
Order By: Relevance
“…Both have been installed in an embankment research facility at Nafferton, Northumberland, UK, to test their abilities against conventional instrumentation ( Fig. 1; for further details, see Hughes et al 2009;Glendinning et al 2014); such facilities are valuable for testing new approaches in a controlled environment. Table 3 identifies three techniques that have been little used so far for monitoring infrastructure slopes and that all show some promise, particularly as more pervasive approaches for condition monitoring of long lengths of asset at relatively low cost.…”
Section: New Measurement Technologiesmentioning
confidence: 99%
“…Both have been installed in an embankment research facility at Nafferton, Northumberland, UK, to test their abilities against conventional instrumentation ( Fig. 1; for further details, see Hughes et al 2009;Glendinning et al 2014); such facilities are valuable for testing new approaches in a controlled environment. Table 3 identifies three techniques that have been little used so far for monitoring infrastructure slopes and that all show some promise, particularly as more pervasive approaches for condition monitoring of long lengths of asset at relatively low cost.…”
Section: New Measurement Technologiesmentioning
confidence: 99%
“…Foundation conditions were stiff to hard Glacial Till with an in-situ permeability ranging from 1x10 -10 -1x10 -12 m/s. Further details of design, construction process, instrumentation and materials testing is provided in Hughes et al [8] The embankment was constructed in four 18 m long sections: the two inner-most sections (panels B and C, 36m long in total, Figure 1) were constructed according to Highways Agency specifications (termed the 'well compacted panels') and simulate new-build highway embankments; the two outer-most sections (panels A and D, Figure 1) were built to represent poorly constructed/heterogeneous rail embankments. This was achieved by placing fill in 1.3 m lifts with minimum tracking by site plant.…”
Section: Test Embankment Construction and Characterisationmentioning
confidence: 99%
“…Anderson et al [4]; Ridley et al [5]; Nyambayo et al [6]; Smethurst et al [7]; Hughes et al [8] and Glendinning et al [3&9] have all identified the role of water (pore water pressures), vegetation and permeability as important parameters in governing the stability of infrastructure slopes of all ages.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of approaches to simulate these effects range from intensity-duration (I-D) threshold envelopes at relatively small scales, to large scale, site based analyses using fully-coupled hydrological-slope stability models (see for example O'Brien et al 2004;Manning et al 2008;Glendinning et al 2006;Rouainia et al 2009;Hughes et al 2009). There are still many gaps in the quality of data and understanding of topography effects, soil properties, precipitation, hydrological properties and changing site conditions through time that limit the usefulness of these fully coupled models).…”
Section: Modelling Landscape Sensitivitymentioning
confidence: 99%